Stratigraphy sequential: definitions, illustrations of the terms and concepts - Cramez, Carlos (2019)
This glossary of Sequential Stratigraphy should not be considered as an attempt to normalize the terminology of Sequential Stratigraphy. The work presented here corresponds, simply, to a compilation of definitions and concepts dispersed in the most varied publications on Sequential Stratigraphy. It is intended, primarily, to serve the young geoscientists who have followed our short courses and workshops, since all the terms defined here were all used in these classes. For each term, presented: (i) a succinct definition (with a translation in French, Portuguese, Spanish, German, Chinese, Russian and Italian which, later, will be updated, particularly the German translation) ; (ii) a tentative geological interpretaion of an auto-traces of a seismic line, a sketch or a photograph illustrating its meaning, and (iii) a commentary, sometimes with notes, clarifying certain points related to the illustration of the term.